Learning Through the Use of Think Smart Games in Mathematics Subjects for Vocational High School Students at PAB Private School, Percut Sei Tuan District, Deli Serdang Regency - Fadilah, Nina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Mathematics learning at the vocational high school (SMK) level is increasingly required to keep pace with modern developments, where students are expected not only to understand theoretical concepts but also to apply them in vocational contexts. SMK students are equipped with specific skills, yet many perceive mathematics as difficult and less relevant to the working world they will face. This often leads to low motivation in learning mathematics. Traditional instruction, which emphasizes the one-way transfer of information from teacher to student, is considered less effective—especially in vocational schools that prioritize hands-on practice. Therefore, an interactive and engaging learning model is needed to develop students’ critical thinking skills. One such approach is the Think–Share–Games model, which encourages students to think independently, collaborate in group discussions, and reinforce understanding through educational games. This model is designed to transform students from passive recipients into active participants in the learning process. In the think stage, students are encouraged to individually comprehend and solve problems. In the share stage, they discuss their thoughts and compare solutions with peers. The games stage tests their understanding through engaging, competitive math-based games. This approach brings learning to life, as students are not merely sitting and listening but also thinking, speaking, and actively participating. Moreover, it allows teachers to assess student comprehension in real time through group interactions. Observations in several classrooms indicate that the Think–Share–Games model significantly increases students’ motivation to learn mathematics and fosters greater enthusiasm throughout each learning phase.